KAJIAN MUTU KIMIAWI TEPUNG TULANG IKAN TUNA SIRIP KUNING (Thunnus albacares) DENGAN SUHU PENGERINGAN YANG BERBEDA - Ade Irma Meulisa; Anhar Rozi; Syarifah Zuraidah; Ikhsanul Khairi (Universitas Teuku Umar, 2021)
Yellow fin tuna (Thunnus albacares) is one type of high economic value fish. The tuna fillet processing itself produces some byproducts including fish bones. The byproduct can be reused as a product and food material. This study aimed to know the chemical quality of the yellow fin tuna bone powder with different drying temperature. The method used were experimental with 3 treatments and descriptive analysis. The treatment of temperature drying (90oC, 105oC, and 120oC), and the method of proximate analyzed refers to SNI. The parameters observed were yield, moisture, ash, protein, fat and calcium content. The result showed that yellow fin tuna bone powder with different drying temperature was best at treatment with value moisture content of P1 = 10.99 %, ash content of P3 = 59.95 %, protein content of P1 = 15.84 %, fat content of P3 = 7.05 %, calcium content of P3 = 20.75% and yield of P1 = 22.92 %.